2022
DOI: 10.3390/antibiotics11070916
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,2,3-Triazole-sulphadiazine-ZnO Hybrids as Potent Antimicrobial Agents against Carbapenem Resistant Bacteria

Abstract: Bacterial pneumonia is considered one of the most virulent diseases with high morbidity and mortality rates, especially in hospitalized patients. Moreover, bacterial resistance increased over the last decades which limited the therapy options to carbapenem antibiotics. Hence, the metallo-β-lactamase-producing bacteria were deliberated as the most deadly and ferocious infectious agents. Sulphadiazine-ZnO hybrids biological activity was explored in vitro and in vivo against metallo-β-lactamases (MBLs) producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The authors used a zinc oxide nanoparticle in combination with sulphadiazine, delivered through aerosolization, to evaluate protection against pneumonia. After 4 days, the bacterial counts in the lungs were reduced and the histopathological signs of inflammation tissue damage were diminished (Aljohani et al, 2022).…”
Section: Rat Infection Modelsmentioning
confidence: 99%
“…The authors used a zinc oxide nanoparticle in combination with sulphadiazine, delivered through aerosolization, to evaluate protection against pneumonia. After 4 days, the bacterial counts in the lungs were reduced and the histopathological signs of inflammation tissue damage were diminished (Aljohani et al, 2022).…”
Section: Rat Infection Modelsmentioning
confidence: 99%
“…The researchers did not provide results from a positive control in their article. Aljohani et al (2022) and coworkers synthesized 1,2,3-triazolesulfadiazine-ZnO hybrids and tested them against three carbapenem-resistant metallo-β-lactamase producing K. pneumoniae (Kp1, Kp5 and Kp8). The synthesized novel sulfadiazines exhibited MIC values between 128 and 256 μg/mL against all three strains.…”
Section: 23-triazole Complexes With Antimicrobial Activitymentioning
confidence: 99%
“…14,66 Strong metal-chelating agents, such as ethylenediaminetetraacetic acid (EDTA), have been shown to inhibit MBLs by removing the metal ions. 81,82 Relevant studies have also been reported as progressive efforts to develop inhibitory agents using nanoparticles, [83][84][85] macrocyclic peptides, 86 and many others. In this study, an overview of the potent small-molecule inhibitors of various bacterial MBLs reported from 2020 to the present, together with their biochemical analyses and mechanism of action are comprehensively presented.…”
Section: Small-molecule Inhibitors Of Mbls: Activity and Mechanisms O...mentioning
confidence: 99%